Implementasi Integrated Marketing Communication (IMC) Space Roastery Coffee Yogyakarta Tahun 2019/2020 - Mitariza Migunani (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
The habit of drinking coffee has actually existed in Indonesia for a long time, but it became a trend that was happening around 2014. The phenomenon of this trend can be seen from the rise of the emergence of coffee shops. A coffee shop is a place that provides a variety of coffee and non-coffee menus. Maintaining a consumer's trust to come back again is an important thing for a company, because customer loyalty is a company's long-term asset. The purpose of this study is to describe the stages in seeing how the implementation of Integrated Marketing Communication is carried out by Space Roastery Coffee. This research method is a qualitative research method and then presented descriptively, namely explaining and describing and describing problems that are closely related to this research. Sources of data in this study were taken from primary data obtained by in-depth interviews and secondary data obtained from books, internet, documents and photo documentation. The results of this study explain that by using integrated marketing or called integrated marketing communications (IMC), which includes the combined efforts of various elements of marketing activities called the marketing communication mix, and has been running effectively which is implemented through advertising (advertising), direct marketing (direct marketing), sales promotion (sales marketing), and public relations (public relations).